Emission of Inorganic PM10 from the Combustion of Torrefied Biomass under Pulverized-Fuel Conditions - Yani, S.; Gao, Xiangpeng; Wu, Hongwei (American Chemical Society, 2015)
This study reports the emission behavior of inorganic particulate matter (PM) with an aerodynamic diameter of <10 μm (PM10) from the combustion of a raw biomass and its torrefied biomass samples under pulverized-fuel conditions. A mallee leaf (~1 cm long × ~1 cm wide), as the raw biomass, was subjected to torrefaction at 220–280 °C to prepare three torrefied biomass samples. After size reduction and fraction to 75–150 μm, the raw and torrefied biomass samples were combusted in a laboratory-scale drop-tube furnace at 1400 °C in air to produce inorganic PM10. The results demonstrate that, in comparison to that of the raw biomass, the combustion of the torrefied biomass leads to considerable reductions in the ash-based (i.e., normalized to equivalent ash input) yields of PM with an aerodynamic diameter of <0.1 μm (PM0.1) as well as Na, K, and Cl in PM0.1, predominantly because of the removal of ~54–77% Cl in the raw biomass during torrefaction. In contrast, the ash-based yields of PM with an aerodynamic diameter of 1–10 μm (PM1–10) as well as Mg and Ca in PM1–10 from the torrefied biomass are substantially higher than those from the raw biomass. On an equivalent energy input basis, which is of more practical relevance, the combustion of the torrefied biomass leads to similar yields of PM with an aerodynamic diameter of <2.5 μm (PM2.5) but considerably higher yields of PM10 than that of the raw biomass.